SO018NON-INVASIVE ASSESSMENT AND MONITORING OF SKELETAL MUSCLE MASS IN CRITICALLY ILL PATIENTS WITH AKI BY QUADRICEPS MUSCLE ULTRASOUND. (6th June 2020) - Sabatino, Alice; Regolisti, Giuseppe; Cantarelli, Chiara; Palladini, Andrea; Di motta, Tommaso; Maggiore, Umberto; Fiaccadori, Enrico
Abstract: Background and Aims: Critically ill patients undergo important muscle wasting during ICU stay, and a significant loss of muscle mass still occurs in the first few days of hospital stay. This may delay both functional recovery and weaning from mechanical ventilation, being also a well-known predictor of mortality. Quite often, muscle wasting is masked by fluid overload, increasing the risk for underestimating the presence of malnutrition, as frequently occurs in critically ill patients with AKI. An important concern in this clinical setting is the lack of adequate tools for routine bedside evaluation of the skeletal muscle mass. Lately, the use of ultrasound (US) for the assessment of muscle mass has aroused considerable interest. It is a non-invasive technique, applicable at the bedside and even in non-collaborative patients, it is economically viable, safe and do not require specialized staff. Recently, its reliability and validity have been demonstrated in critically ill patients with AKI. On this premise, in the present study, we aimed to evaluate the clinical application of US for both evaluation and monitoring of quadriceps muscle thickness in critically ill patients with AKI. Method: This is an observational study, conducted in the renal ICU of the Parma University Hospital. All adult patients with AKI, with no distinction regarding the severity of AKI, admitted in the renal ICU from 15/03/2017 to 15/03/2018, with previous hospital stay less than 72h, with a likely ICU stay of at least 5 days were eligible for entering the study. The diagnosis of AKI was made according to KDIGO. Quadriceps rectus femoris and vastus intermedius thickness (QRFT and QVIT) were measured at the midpoint and at the border between the upper third and lower two-thirds between the anterior superior iliac spine (ASIS) and the upper pole of the patella. US was performed twice during ICU stay, i.e., at baseline (within 72h from admission) and after 5 days since the first measurement. Results: We enrolled 30 patients, 70% (n= 21/30) were male, mean age ± SD age 74±11 years, APACHE II mean ± SD, 22 ± 5. Ultrasonography took less than 10 minutes to set up and complete image acquisition and less than 10 minutes per image to complete measurement analysis in all patients. A total of 472 images were analyzed across the 30 subjects.